Compensatory Liability of Healthcare Professionals in the Criminal Offense of Unconscious Treatment in the Republic of Croatia - Galiot, Mijo; Brizić Bahun, Vanesa (Medicine, Law & Society, 2022)
The authors analyze the issue of the availability and effectiveness of a legal mechanism for resolving the consequences of injuries in health care, so the focus of the paper is primarily the liability of healthcare professionals, as patients are guaranteed, among other rights, the right to compensation for medical intervention. As liability for damages can be decided not only in civil (litigation) proceedings but also in adhesion proceedings associated with criminal proceedings conducted for the criminal offense of negligent treatment, the basic term of medical error is defined, pointing out the basic features of the criminal offense of negligent treatment with emphasis on the issue of the responsible person and their guilt. The founding assumptions of liability for damages are also presented, with an emphasis on the same issues in both litigation and adhesion proceedings. Furthermore, with regard to the setout provisions and general principles, the effectiveness of the compensatory claim in the criminal offense of negligent treatment is analyzed, and at the same time several specific issues are addressed and suggestions for possible solutions are given.